Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1007/s15010-022-01850-7
|View full text |Cite
|
Sign up to set email alerts
|

Is remdesivir safe in patients with renal impairment? Experience at a large tertiary urban medical center

Abstract: Purpose Remdesivir is FDA-approved for treatment of patients hospitalized with COVID-19 pneumonia, but not recommended in patients with severe renal failure. This study aims to evaluate the safety of remdesivir in this patient population. Methods This was a single-center, retrospective cohort study including patients ≥ 18 years old, admitted between May 1, 2020 and April 30, 2021 who received remdesivir. Patients were divided into two groups: estimated creatinine cleara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…In a study of 416 patients in New York, 55 patients had renal impairment with CrCl (eCrCl) < 30 mL/min, and there was no significant difference in the incidence of AKI and hepatotoxicity compared to those without. 19 In this study, the definitions of renal injury and hepatic injury were different from our study, so there may be differences in the results. In addition, a study investigating 46 patients with renal impairment using remdesivir in India concluded that remdesivir was well tolerated by patients with AKI or chronic kidney disease.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…In a study of 416 patients in New York, 55 patients had renal impairment with CrCl (eCrCl) < 30 mL/min, and there was no significant difference in the incidence of AKI and hepatotoxicity compared to those without. 19 In this study, the definitions of renal injury and hepatic injury were different from our study, so there may be differences in the results. In addition, a study investigating 46 patients with renal impairment using remdesivir in India concluded that remdesivir was well tolerated by patients with AKI or chronic kidney disease.…”
Section: Discussionmentioning
confidence: 56%
“… 18 In addition, a retrospective study conducted at a hospital in New York found that remdesivir was not associated with acute kidney injury (AKI) or hepatotoxicity in patients with estimated creatinine clearance (eCrCl) < 30 mL/min compared to those with eCrCl ≥ 30 mL/min. 19 However, safety data on remdesivir in real-world clinical situations, particularly in vulnerable populations, are insufficient. Few studies have investigated the safety of remdesivir in renal impairment patients.…”
Section: Introductionmentioning
confidence: 99%
“…Our series showed that peak SCr ratios were on Day 3, corresponding to their report. Sunny and others [7], however, reported that remdesivir was not associated with the development of AKI or hepatotoxicity in patients with an estimated creatinine clearance < 30 mL/min.…”
Section: Discussionmentioning
confidence: 93%
“…We assessed the following background status parameters: (1) eGFR < 30 ml/min/1.73 m 2 , (2) SCr ratios to baselines > 1.5, (3) SCr ratios to upper limits > 1.5 (Grade 2), (4) ALT ratios to upper limits > 5 (Grade 3), (5) remdesivir administration > = 4 days, (6) sex, (7) age, (8) height, (9) weight, (10) use of dexamethasone, and (11) number of SARS-CoV-2 vaccinations. We used Excel 2019 software (Microsoft Inc., Redmond, WA, USA) to generate line graphs depicting the time course of laboratory data.…”
Section: Methodsmentioning
confidence: 99%
“…As a well-known class of antiviral agents, nucleoside analogs that function by targeting the conserved active site of viral polymerase have been of research interest in the discovery of antiviral drugs. In recent years, two nucleoside drugs, remdesivir 2 and molnupiravir, 3 used for treating COVID-19 have been marketed, and their application may be further expanded due to their broad-spectrum antiviral properties. 4,5 β-D-N 4 -Hydroxycytidine (NHC, EIDD-1931), a cytidine analog, is the parent nucleoside of molnupiravir (EIDD-2801) (Fig.…”
Section: Introductionmentioning
confidence: 99%